The agency relationship problems in small business lending - Mahmood, Rosli (2001)
The agency contract has been identified as a major source of problematic relationship between bankers and the small business owners.The problems which arise from this relationship, such as asymmetry of information, moral hazard and' adverse selection, cause difficulties for banks to channel the required funds to the small business sector.To overcome these problems, banks require greater level of compensation and protection, such as charging high interest rates, asking for higher collateral requirements, and or imposing some conditional features in the loan contract. However, it is suggested that these bankers need to focus more on understanding small businesses so that the potential of these businesses can be identified for viable funding.